1989
DOI: 10.1176/ajp.146.4.513
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of desipramine in 18 men with posttraumatic stress disorder

Abstract: Eighteen male U.S. veterans meeting DSM-III criteria for posttraumatic stress disorder (PTSD) completed a 4-week double-blind, crossover study comparing administration of 200 mg/day of desipramine with placebo. Response was measured by using the Beck Depression Inventory, the Hamilton Rating Scale for Depression, the Hamilton Rating Scale for Anxiety, and the Impact of Event Scale. Overall, the only apparent response to desipramine was in some symptoms of depression; there were no changes in anxiety and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Data with desipramine are mixed, with one RCT showing significant benefit, which were comparable to paroxetine [970], and the other showing improvements in depression only [995]. While RCTs with the TCAs suggest some benefit with these agents, it appears to be limited.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…Data with desipramine are mixed, with one RCT showing significant benefit, which were comparable to paroxetine [970], and the other showing improvements in depression only [995]. While RCTs with the TCAs suggest some benefit with these agents, it appears to be limited.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…Tricyclic antidepressants, which block presynaptic reuptake of serotonin and NE, such as amitriptyline (J. Davidson et al, 1990), imipramine (Kosten, Frank, Dan, McDougle, & Giller, 1991) have demonstrated to be superior to placebo for the treatment of PTSD; although there was also a negative RCT with desipramine (Reist et al, 1989). In another study, paroxetine did not show statistical superiority to desipramine, but desipramine was superior to paroxetine with respect to study retention and alcohol use outcomes (Petrakis et al, 2012).…”
Section: Monoaminergic Systemmentioning
confidence: 99%
“…This then left 154 full-text articles which were read and 39 were removed as not meeting the inclusion criteria. A total of 115 studies were included for our series of pharmacological reviews ( Figure 1 ); with 49 studies (Baker et al, 1995 ; Brady et al, 2000 , 2005 ; Braun, Greenberg, Dasberg, & Lerer, 1991 ; Butterfield et al, 2001 ; Carey, Suliman, Ganesan, Seedat, & Stein, 2012 ; Connor, Sutherland, Tupler, Malik, & Davidson, 1999 ; Davidson, 2004 ; Davidson et al, 2006 ; Davidson, Brady, Mellman, Stein, & Pollack, 2007 ; Davidson et al, 2005 , 1990 ; Davidson, Rothbaum, & Tucker, 2006 ; Davidson, Rothbaum, van der Kolk, Sikes, & Farfel, 2001 ; Davidson et al, 2003 ; Davis et al, 2008 , 2004 ; Dunlop et al, 2017 ; Feder et al, 2014 ; Friedman, Marmar, Baker, Sikes, & Farfel, 2007 ; Hertzberg et al, 1999 ; Hertzberg, Feldman, Beckham, Kudler, & Davidson, 2000 ; Katz et al, 1994 ; Kosten, Frank, Dan, McDougle, & Giller, 1991 ; Kwako et al, 2015 ; Li et al, 2017 ; Marshall, Beebe, Oldham, & Zaninelli, 2001 ; Marshall et al, 2007 ; Martenyi, Brown, & Caldwell, 2007 ; Martenyi, Brown, Zhang, Prakash, & Koke, 2002 ; Matthew et al, 2011 ; Padala et al, 2006 ; Panahi et al, 2011 ; Pfizer588 – sertraline ; Rasmusson et al, 2017 ; Reist et al, 1989 ; Shalev et al, 2011 ; Shestatzky, Greenberg, & Lerer, 1988 ; SKB627, Bryson, Lawrinson, GJ, & KM, unpublished ; SKB650, Bryson, KE, & Jeffery, unpublished ; Sonne et al, 2006 ; Tucker et al, 2003 , 2007 , 2001 ; van der Kolk et al, 1994 , 2007 ; Villarreal et al, 2016 ; Yeh...…”
Section: Resultsmentioning
confidence: 99%